Pengaruh Pajak Pertambahan Nilai Dan Pajak Penjualan Atas Barang Mewah Terhadap Daya Beli Konsumen Kendaraan Bermotor (Studi Kasus Kendaraan Bermotor Roda Empat) - Anissa Rosiana; Ratih Kumala (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The number of motorized vehicles such as sedans, jeeps, minibuses, as well as trucks and pickups, experienced an increase in 2021. Value Added Tax and Sales Tax on Luxury Goods (PPnBM) are imposed to balance the tax burden on low-income consumers and high-income consumers. The purpose of this research is to determine the effect of value added tax and sales tax on luxury goods on the purchasing power of motorized vehicle consumers. The research was conducted using quantitative methods with data collection through questionnaire distribution. The research population was 100 taxpayers of four-wheeled motor vehicles, with a sample of 50 respondents who were selected using the Slovin formula. The results showed that based on the results of the t-test, the p-value (significance level) of the value added tax is 0.002, which means that the value added tax has a significant positive effect on the purchasing power of four-wheeled motorized consumers, so H1 is rejected. The p-value of sales tax on luxury goods is 0.000, which means that sales tax on luxury goods has a significant positive effect on the purchasing power of consumers of four-wheeled motor vehicles, so H2 is accepted. Meanwhile, the results of the f test produce a p-value (significance level) of 0.000, which means that the value added tax and sales tax on luxury goods simultaneously have a significant positive effect on the purchasing power of consumers of four-wheeled motor vehicles, so H3 is accepted.